We are silently paving the way toward human–wildlife coexistence: The role of women in the rural landscapes of southern Andes - Almuna, Rocío; Cortés, Josefina; Medina, María de los Ángeles; Vargas, Solange P. (Frontiers in Conservation Science, 2022)
Gender plays an important role in human–wildlife coexistence. Women have their own distinct form of environmental knowledge; women shape attitudes and perceptions related to wildlife and influence the use of natural spaces and the nature of human–wildlife interactions. Being a female farmer or practitioner involved in human–wildlife conflict mitigation poses a variety of obstacles and benefits. The way conservation conflicts are perceived and managed is gendered, and this needs to be taken into account when working with local communities to achieve effective and fluent dialogue, planning, implementation, and evaluation. The existing body of evidence is focused mainly in Africa and Asia and suggests that the sharing of landscapes between humans and wildlife has different implications for men and women with respect to their attitudes toward wildlife and how they are impacted by it. Although extensive research has been done in relation to gender, conservation, and natural resource management, the gender perspective of human–wildlife coexistence is underreported. Feminist political ecology emphasizes that gender differences originate in the need to overcome existing social and political barriers and is highlighting the importance of en-gendering research. In Chile, work in the rural sector poses various challenges, especially for women. Rural landscapes are, in general, dominated by men, with low female participation in decision-making spaces. Nonetheless, this appears to be silently changing. In this perspective, we contrast three undocumented experiences of our work as female researchers and facilitators of human–wildlife coexistence (northern case, central case, and southern case). The aim of this perspective piece is to expose current findings for the role of women in human–wildlife coexistence, contrast these with our reports, and propose future directions.